Cross sectional association of nutrition intake and caracteristic with nutritional status of HIV patients - Wahyuni, Endang Sri; J, Yulia Novika; Sutrio, Sutrio (Institute of Computer Science (IOCS), 2025)
Nutritional status is associatesd with both quality of life and mortality risk in individuals with HIV. Adequate nutrition intake enhance resilience againts opportunistic infections in HIV patients. The aim of this study is determine factors associated with nutritional status. This study was using cross sectional design that involved 99 participants that were determined by consecutive sampling. The participants were HIV patients who were outpatient at Kanca Sehati Polyclinic, Dr Hi Abdul Moeloek Hospital, Lampung on Juli – August 2024. The dependent variable is nutritional status and the independent variables are the characteristics and nutrition intake of HIV patient. Nutritional status is determined by calculating Body Mass Index (BMI), characteristic data were colected from medical records and interviews, nutrition intake form SQ FFQ (Semi Quantitative Food Frequency). Data were analyzed by chi square. The results of this study show that the common range of age is 21 – 40 years old (78.78%), the common education level is secondary education (62%), the majority of participants' occupation was self-employment (29%). Participants received ART treatment <1 year are 50%, and 12% of participants have gastrointestinal disorders. Participants with underweight are 27% and overweight are 13%. Participants who have energy intake deficit are 37%, protein intake category are 54%. The statistical tests show that nutritional status are related to type of work (0.003) and medication consumed (p=0.015), nutritional status is not associated with gender, age, education, employment, duration of taking medication, energy intake or protein intake.